1996
DOI: 10.1212/wnl.46.3.802
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of nigrostriatal denervation on the gamma-aminobutyric acidic neurons of substantia nigra pars reticulata and superior colliculus in parkinsonian syndromes

Abstract: To examine the effects of nigrostriatal denervation on the substantia nigra pars reticulata (SNpr), one of the main outputs of the basal ganglia, we used quantitative in situ hybridization to analyze the messenger RNA coding for Mr 67,000 glutamic acid decarboxylase (GAD67 mRNA) in the SNpr neurons from patients with Parkinson's disease (PD), monkeys rendered parkinsonian by 1-methyl-4- phenyl-1,2,3,6-tetrahydropyridine (MPTP), and their respective controls. In MPTP-intoxicated monkeys, the expression of GAD67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 13 publications
5
45
0
Order By: Relevance
“…The time interval between the death of the patients and conservation of the brain tissues did not affect G D N F mRNA, since, under similar conditions, the probe allowed detection of G D N F m R N A in a newborn infant striatum also obtained post mortem. In addition, the absence of staining observed in the control and parkinsonian brains used in this study cannot be attributed to a global mRNA degradation since glutamic acid decarboxylase (isoform 67 KD) mRNAs (Levy et al, 1995a;Vila et al, 1996), several glutamate receptors mRNAs (Bernard et al, 1996), substance P and methionin-enkephalin mRNAs (Levy et al, 1995b) have been successfully detected by in situ hybridization in the studied brains. It cannot be excluded however that GDNF mRNA is particularly instable post mortem.…”
Section: G D N F M R N a In Parkinson's Diseasementioning
confidence: 70%
“…The time interval between the death of the patients and conservation of the brain tissues did not affect G D N F mRNA, since, under similar conditions, the probe allowed detection of G D N F m R N A in a newborn infant striatum also obtained post mortem. In addition, the absence of staining observed in the control and parkinsonian brains used in this study cannot be attributed to a global mRNA degradation since glutamic acid decarboxylase (isoform 67 KD) mRNAs (Levy et al, 1995a;Vila et al, 1996), several glutamate receptors mRNAs (Bernard et al, 1996), substance P and methionin-enkephalin mRNAs (Levy et al, 1995b) have been successfully detected by in situ hybridization in the studied brains. It cannot be excluded however that GDNF mRNA is particularly instable post mortem.…”
Section: G D N F M R N a In Parkinson's Diseasementioning
confidence: 70%
“…Possibly, the antiparkinsonian effects of D 1 agonists are dependent upon neuronal excitation produced in the cell body (Gonon 1997), as well as modulation of neurotransmitter release at the terminal, the combination of which results in an increase in GABA release in SNr. It has been suggested that the hyperactivity of SNr cells is involved in the production of parkinsonian symptoms (Vila et al 1996), and that the SNr is a critical region for the generation of tremulous movements (Buzsaki et al 1990;Finn et al 1997b;Salamone et al 1998). SNr neuronal activity can be reduced by systemic (Weick et al 1990) or nigral (Timmerman and Abercrombie 1996) administration of a D 1 agonist.…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia are organised in such a fashion that nigrostriatal denervation (the hallmark of Parkinson's disease) leads to overactivity of the internal globus pallidus and the substantia nigra pars reticulata (Fig. 4, right) [74,190]. The pathological hyperactivity of both these nuclei and the subthalamic nucleus [191] has been seen as the result of a reduced inhibitory input from the striatum to the direct pathway [109] and increased activity of the indirect pathway [71].…”
Section: The Basal Gangliamentioning
confidence: 99%